Modern ways of improving the procedure for the formation and verification of digital signature - Ільєнко, А.В.; Миронова, Г.О. (Science-based technologies, 2018)
In the article, a comparative analysis of existing algorithms for the formation and verification of the digital signature has been carried out, namely, widespread algorithms and the criteria for comparison was the mathematical basics on which the algorithm is based and the size of the public key. Based on the analysis, it is established that there are schemes with the addition of messages and schemes with the restoration of the information message. The conducted studies made it possible to determine that the schemes with message recovery differ from the schemes with the addition that they do not completely hash messages, but instead use masking functions and redundancy of the message. It was determined that the most effective and optimal for further use is the Nimberg-Ruppel scheme, which is based on elliptical curves (ECNR). The article describes the theoretical basis for creating a system for ensuring the integrity, reliability and confidentiality of information based on digital signatures based on elliptical curves using the standard DSTU 4145-2002 with the possibility of restoring an information message based on ECNR.